The sea child : a novel - Wilgus, Linda (Ballantine Books, 2026)
"In this enchanting, adventurous debut novel, a band of seafaring smugglers lands on the Cornish coast, where a young widow with a mysterious past becomes entangled in their schemes--and with their charismatic captain. England, early 1800s: Destitute and forced to leave her home in London, Isabel, a young widow of the Napoleonic Wars, returns to the village on the rugged Cornish coast where she was found as a small child, dripping wet and alone. Hoping to learn more about her enigmatic origins, she's shocked to find herself at the center of a local legend claiming that she is the daughter of a sea spirit. As Isabel adjusts to life in her rented cottage, the coast is rife with smugglers and the Revenue Officers who hunt them. One evening, a group of dangerous raiders arrives at her door, carrying their wounded captain, Jack. Remembering her late husband's fatal injuries, Isabel decides to care for Jack and soon feels a powerful connection to him. Even after Jack recovers, Isabel finds herself unable to forget him. Meanwhile, the sea calls to her, and a Revenue Officer who likes to hang smugglers poses a threat in more ways than one. Before long, Isabel finds herself caught on the wrong side of the law, with violence and heartbreak looming. From the coves of Cornwall to the wild coast of Brittany, during perilous raids at sea and society dinner parties, Isabel fights to understand her kinship with the ocean while seeking answers about her past. But when the threat catches up with them and Jack's life hangs in the balance, she must draw on all her courage and delve deep into the mythical heart of the Cornish coast. For only a sea child can turn the tide . . ." -- (dust jacket)